The Effect Of Using A Strategy (5E,S) On The Achievement Of Intermediate Third-Grade Students In The History Course - Suaad salman Hassan , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study aimed to identify the effectiveness of using the Five Yards strategy in teaching history in achievement among third-grade students, and the researcher used the experimental method according to the design of the two dimensional experimental and control groups. One of them is the experimental group (30) students and the other is the control group (30) students, and the study was implemented during the first semester of the academic year (2016/2017). Statistically significant differences at the level of (0.05) in favor of the experimental group in achievement and the most important conclusions. Teaching according to the Five Y's strategy helps students to develop interaction between them and the teacher and students. The effect of using the five-yards strategy in raising the level of achievement of third-grade intermediate students in the subject of modern and contemporary history of the Arab world compared to the usual method for historical facts and information. It made the students more active and vital throughout the lesson. Through the findings of this study, the researcher has reached